Covid-19: Pandemia de violencia doméstica - Tatiana Stoianova; Liudmyla Ostrovska; Grygorii Tripulskyir (Universidad Hemisferios, 2020)
The article is devoted to the analysis of domestic violence in the context of Covid-19. The research is carried out for the first time in the focus of several sciences: psychology, sociology, and jurisprudence. To study the legal regulation of domestic violence, knowledge from different branches of law was used: international, criminal, administrative, and civil procedural law. Attention was paid to the historical retrospective—how the concept of domestic violence first appeared at the world level, and how it was differentiated and implemented in the national legislation of the participating countries. The problems of signing the Istanbul Agreement are highlighted. Special attention was paid to the current wave of domestic violence as a result of the Covid-19 pandemic. The prerequisites of a general psychological, social, and economic nature, their interdependence, and connection with the pandemic were investigated. The scale of the scourge of domestic violence in the context of a pandemic in different countries is indicated, and its short-term and long-term consequences for the well-being of the nation. The specific mechanisms for preventing family violence at three levels are considered: general criminogenic, a comprehensive mechanism for preventing violence at the level of interaction between the state and public organizations, and directly special means. The study concludes that Covid-19 pandemic has a direct impact on the exacerbation of domestic violence. The solutions are proposed, from legislative amendments to the redistribution of state and public forces to address the problem of domestic violence.